Efficacy of prophylactic dexamethasone in prevention of postoperative nausea and vomiting - Leila Sekhavat; Robab Davar; Shekoufeh Behdad (Springer, 2019)
Objective: Many trials have been conducted with regard to the relative benefits of prophylactic anti-emetic interventions given alone or in combination, yet the results remain unknown. This study reviewed the efficacy of a single prophylactic dose of dexamethasone on postoperative nausea or vomiting (PONV) after abdominal hysterectomy. Methods: In a prospective study of 100 women undergoing total abdominal hysterectomy (TAH) under general anesthesia, the dexamethasone group (n = 50) received a single dose (8 mg) immediately after the operation, and the saline group (n = 50) received a dose of saline as a placebo, in addition to conventional management. The incidence of nausea, vomiting, the need for an anti-emetic and patient satisfaction with the management of PONV were evaluated during the first 24 postoperative hours. Results: The overall frequency of nausea during the initial postoperative 24 in the dexamethasone and saline groups were 12% and 18%, respectively, and vomiting was 10% and 16%, respectively (P = 0.001). However, there was a lower need for a rescue anti-emetic drugs in the dexamethasone group (18% vs 24%), but it was not statistically significant (P = 0.06). Conclusion: The results of this study indicate that a single prophylactic dose of dexamethasone after an operation can reduce postoperative nausea and vomiting.